Get a Job, You Tramp! Deviance and Stigma in the Work of Street Artists and Its Organizing Implications - Sampaio, Ana Carolina; Bispo, Marcelo de Souza (Organizações & Sociedade, 2022)
The aim of the current study is to analyze the work of street (circus) performers at traffic lights, from a sociological perspective. Therefore, this article focuses on contributing to improve debates about work, by going beyond the individualistic psychological perspective prevailing in the Business Management field and in organizational studies. By assuming work as social practice arising from organizing processes, it uses the classic concepts — deriving from Sociology — of stigma and deviance, as well as takes a critical position about neoliberal rationality, to theoretically contribute to process to think about work based on a non-traditional logic. It analyzes organizations outside organizations, such as family, the streets and the city. The main findings observed in the current study, based on eighteen semi-structured interviews conducted with street artists, enabled seeing that stigmas, such as tramps and filthy people, imposed on these artists, as well as difficulties in their relationship with their families, are the main obstacles to the type of work carried out by them. It was possible concluding that market-oriented neoliberal rationality, which appropriates people’s work and turns profit maximization into the very rationality of life, contributes for circus artists who work at traffic lights to be considered deviant and stigmatized, as well as opens room for angry discourses capable of promoting violence and prejudice. Thus, it is necessary changing the “get a job, you tramp!” statement into understanding of and respect for different individuals.